The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Oxford Research Encyclopedia of Anthropology 2022
DOI: 10.1093/acrefore/9780190854584.013.198
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Adhesives

Abstract: An adhesive is any substance that bonds different materials together. This broad definition includes materials used in everything from hafted stone tools to monumental architecture. In addition, the combination of bonding, plasticity, and insolubility meant that some adhesives were exploited for waterproofing and sealing of materials, as self-adhering inlays and putties, and as paints, varnishes, and inks. Adhesives have a history of at least 200,000 years. Throughout (pre)history and around the world, people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 196 publications
0
2
0
Order By: Relevance
“…Small amounts of birch pitch can be common at European archaeological sites (Jensen et al 2019;Kashuba et al 2019;Mazza et al 2006;Ottoni et al 2021;Rageot et al 2021;Sykes 2015). Although birch pitch is not found in North American archaeological sites, other plant pitches, adhesives, and gums are found that could contain similar materials and genetic traces as birch pitch (Fox et al 1995;Langejans et al 2022). Pitches can be found with tooth and tool marks and, in some cases, fingerprints (Aveling and Heron 1999;Kashuba et al 2019;Sykes 2015).…”
Section: Birch Pitch and Other Chewed Materialsmentioning
confidence: 99%
“…Small amounts of birch pitch can be common at European archaeological sites (Jensen et al 2019;Kashuba et al 2019;Mazza et al 2006;Ottoni et al 2021;Rageot et al 2021;Sykes 2015). Although birch pitch is not found in North American archaeological sites, other plant pitches, adhesives, and gums are found that could contain similar materials and genetic traces as birch pitch (Fox et al 1995;Langejans et al 2022). Pitches can be found with tooth and tool marks and, in some cases, fingerprints (Aveling and Heron 1999;Kashuba et al 2019;Sykes 2015).…”
Section: Birch Pitch and Other Chewed Materialsmentioning
confidence: 99%
“…We further define ‘resin’ as a viscous hydrophobic exudate, primarily composed of terpenes and collected directly from a tree or plant without the need for initial thermal processing, although this does not preclude secondary processing (Modugno et al 2006; Pollard & Heron 2015). Pitch and tar are sometimes used interchangeably, with ‘pitch’ often used to describe the solid/semi-solid portion of resins and tars, but confusingly sometimes used to refer to the tapped resin from certain trees (Langejans et al 2022), which is why it occurs frequently within archaeological and ethnographic texts. To avoid confusion, other than the appearance of ‘pitch’ within our ethnographic data tables, which respects the original published wording, we will avoid using this term.…”
Section: Introductionmentioning
confidence: 99%